Cabinet size, power-sharing and ethnic exclusion in Africa - (:unkn) unknown (My University, 2021)
While it is often pointed out that African countries have large government cabinets that underpin economic performance, lesser is known about the factors behind the size of government cabinets in Africa. Using an original database of the number of ministerial appointments in government offices in 35 African states, this paper establishes a robust negative relationship between the size of the government cabinet and the exclusion based on ethnicity. This result suggests that the governments that are more inclusive tend to be the largest, independent to the number of ethnic groups present in the country, namely, the state of the ethno-linguistic fractionalization. However, the results also show that this inclusion is in favor of powerless positions, suggesting that inclusion might be less about power-sharing than it is about resource-sharing, since the incumbent controls the key positions, while the included ethnic groups have peripheral positions with, however, an access to public rents. The results are robust to various sensitivity analyses.
Keywords: African Research